Transarterial embolization in management of post-traumatic hematuria - Chataut, Dinesh; Suwal, Sundar; Thapa, Ajit; Chaudh, Ranjit; Ghimire, Ram Kumar (Journal of Society of Surgeons of Nepal, 2019)
Introduction: Iatrogenic injuries are the most common (>50%) cause of renal vascular lesions and most of these vascular lesions resolve spontaneously, however, surgical or percutaneous treatment is recommended when there is massive bleeding, renal hemorrhage persisting for more than 72 hours, or progressively deteriorating renal functions. Renal artery embolization is considered safe, effective as well as less invasive as the alternative treatment method is emergent nephrectomy or clamping of the renal artery which results in the loss of the kidney. We conducted a study to describe the efficacy of transarterial embolization in the management of post-traumatic hematuria. Methods: Retrospective review of 30 patients from April 2013 to July 2017 who underwent transarterial embolization for renal vascular lesions following blunt and iatrogenic renal injuries was done. Type of renal vascular lesions, the angiographic status of visualized vascular lesions immediately following embolization, and post-procedural status of hematuria were evaluated. Results: Thirty patients with a mean age of 35.3 years were included in the study. Twenty-two patients with pseudoaneurysm and eight with arteriovenous fistula in the kidney underwent transarterial embolization. Selective embolization was done in 28 out of 30 patients with complete resolution of hematuria. Two patients underwent non-selective embolization of the main renal artery which was necessary for control of hematuria. Conclusions: Transarterial embolization is a highly effective technique in the management of traumatic renal vascular lesions presenting with left threatening or continuous hematuria.